1997
DOI: 10.1159/000262381
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Three-Year Caries Protection from an Aluminium-Containing and a Fluoride-Containing Toothpaste

Abstract: In the present study, 2,087 fifth-graders (mean age: 12 years) from two cohorts entered a 3-year clinical toothpaste trial. The study subjects were randomly allocated to two groups: one group was a positive control using a 0.83% NaFPO3 toothpaste, while the other group brushed with a test toothpaste containing 1.77% KA1(SO4)2. Both toothpastes were used unsupervised at home. One set of bite-wing radiographs was obtained at the beginning of the trial and another at the 3-year fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…hRuiken et al 1986; Isogangas et al 1993; Sköld et al 1994; Heidmann and Poulsen 1997; Morgan et al 1998; Alanen et al 2000; Sköld et al 2001; Bruno-Ambrosius et al 2005; Källestål 2005; David et al 2006; Heyduck et al 2006; Foster Page and Thomson 2012; Holmén et al 2013.…”
Section: Resultsmentioning
confidence: 99%
“…hRuiken et al 1986; Isogangas et al 1993; Sköld et al 1994; Heidmann and Poulsen 1997; Morgan et al 1998; Alanen et al 2000; Sköld et al 2001; Bruno-Ambrosius et al 2005; Källestål 2005; David et al 2006; Heyduck et al 2006; Foster Page and Thomson 2012; Holmén et al 2013.…”
Section: Resultsmentioning
confidence: 99%
“…They developed this view further by carrying out a clinical trial and described an anticaries e¡ect of rinses containing 500 ppm aluminum [62]. However, the results of a recent 3-year caries protection study [51] of 2087 school children in Denmark indicated that a toothpaste containing 1.77% KAl(SO 4 ) 2 was less e¡ective in reducing caries than a positive control paste containing 0.83% NaFPO 3 . A paste containing both £uoride and aluminum might have been more e¡ective than ones with single agents, in keeping with the view that a large part of the anticaries action of £uoride involves antimicrobial e¡ects.…”
Section: Metal Complexes and E¡ects On Phosphoryl Transfermentioning
confidence: 99%
“…They developed this view further by carrying out a clinical trial and described an anticaries effect of rinses containing 500 ppm aluminum [62]. However, the results of a recent 3‐year caries protection study [51] of 2087 school children in Denmark indicated that a toothpaste containing 1.77% KAl(SO 4 ) 2 was less effective in reducing caries than a positive control paste containing 0.83% NaFPO 3 . A paste containing both fluoride and aluminum might have been more effective than ones with single agents, in keeping with the view that a large part of the anticaries action of fluoride involves antimicrobial effects.…”
Section: New Information On Physiological Actions Of Fluoride On Micmentioning
confidence: 99%